Alternative aluminum-based cocatalysts for the iron-catalyzed oligomerization of ethylene1. Issue 29 (7th August 2015) - Boudier, Adrien; Breuil, Pierre-Alain R.; Magna, Lionel; Olivier-Bourbigou, Hélène; Braunstein, Pierre
<x xml:space="preserve">Abstract</x> Multinuclear aluminum cocatalysts have been obtained by the reaction of various phenols, alcohols or diols with trimethylaluminum and were used in situ or as isolated, well-defined species, for the activation of an iron(ii) or an iron(iii) pre-catalyst for the oligomerization of ethylene.